Creating thinking classrooms leading educational change for this century - Gini-Newman, Garfield; Case, Roland 1951- (Corwin, 2018)
"This is a book for school leaders in a broad sense: anyone in schools who wishes to take a leadership role whether district leaders, principals, curriculum specialists, department heads, or coaches. Anyone who leads and supports teachers. The book focuses on separating the rhetoric of school reform from the reality, analyzing what is actually happening, and offering advice that teachers can use. The reform movement shifts are threefold: 1. Reorient teaching beliefs from a discovery or didactic classroom to that of a thinking classroom 2. Focus attention on more enriched versions of the traditional education goals. Move from fostering knowledge to deep understanding, from skills to real-life competencies, and from attitudes to genuine commitments 3. Align teaching with 5 key principles- engage students, sustain inquiry, nurture self-regulated learners, create assessment rich learning, and enhance learning through digital technology This book is loaded with examples, stories, reflections, and action steps. A key attitude throughout the book is many of the changes that are being called for are already in place but need to be sharpened. There is often a need to renovate rather create a revolution. The proposed changes can be useful for teachers to affirm what they do well, refine their practice, and aspire to more substantial changes in areas that need renovation"--Provided by publisher.